An absorbable hemostatic material based on self-assembly of plant polyphenol and silk fibroin and a preparation method thereof

CN122998446APending Publication Date: 2026-10-30佘睿
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611519390.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-29
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

本发明摒弃传统单一pH静态混合模式,采用分段梯度酸碱调控,诱导丝素蛋白分子从无规卷曲逐步向β-折叠有序构象转变,同时驱动复合多酚分子逐层锚定在蛋白网络中,形成表层大孔快速吸液、内层微孔锁血固凝的双层分级多孔结构,孔隙率可控,解决传统材料孔隙无序、吸液慢、锁血差的问题;突破单一单宁酸多酚体系,采用单宁酸与没食子酸复配,兼顾极速凝血与创面微环境调控;本发明引入微量生物相容性铁和钙复合离子,与复合多酚实现原位动态螯合交联,构建“蛋白氢键网络+金属多酚螯合网络”双交联体系,显著提升材料湿态力学强度、创面粘附性,同时钙离子可主动激活凝血通路,双重加速止血,铁离子辅助抑菌抗氧化,功能协同增效

Benefits of technology

[0018]优选地,所述步骤(1)中得到的高纯丝素蛋白溶液的纯度应大于或等于98%。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122998446A_ABST
    Figure CN122998446A_ABST
Patent Text Reader

Abstract

The application discloses an absorbable hemostatic material based on self-assembly of plant polyphenol and silk fibroin and a preparation method thereof and belongs to the technical field of hemostatic materials. The absorbable hemostatic material comprises the following components in parts by weight: 90-100 parts of high-purity silk fibroin solution, 4-6 parts of composite plant polyphenol, 14-20 parts of composite biological metal ion aqueous solution, and the balance of deionized water. The application discloses abandoning the traditional single-pH static mixing mode, adopting segmented gradient acid-alkali regulation, inducing the ordered transformation of the conformation of silk fibroin, realizing the layer-by-layer anchoring of polyphenol, and constructing a hierarchical porous structure with large pores for absorbing liquid on the surface layer and micro-pores for locking blood in the inner layer. Tannic acid-gallic acid is compounded, and iron and calcium composite ions are in-situ chelated to form a hydrogen bond-chelation double-crosslinking network, so that the wet strength and adhesion are improved, and the effects of promoting coagulation and hemostasis, inhibiting bacteria and resisting oxidation are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of hemostatic materials technology, specifically referring to an absorbable hemostatic material based on the self-assembly of plant polyphenols and silk fibroin and its preparation method. Background Technology

[0002] Acute traumatic bleeding and intraoperative wound bleeding are common problems in clinical surgery, emergency care, and battlefield medicine. Rapid and efficient hemostasis, inhibition of wound infection, and promotion of tissue repair are the core development needs of medical hemostatic materials. Currently, the mainstream absorbable hemostatic materials in clinical practice mainly include gelatin sponges, chitosan dressings, oxidized cellulose, and monofilament protein hemostatic materials. Although they can achieve basic hemostasis, they generally have drawbacks such as slow hemostasis rate, low wet mechanical strength, poor wound adhesion, lack of anti-inflammatory and repair functions, and a mismatch between the in vivo degradation cycle and wound healing. They are difficult to adapt to the needs of high-pressure active bleeding, irregular cavity wounds, and delicate surgical wounds.

[0003] Silk fibroin possesses excellent biocompatibility, biodegradability, and cell adhesion, making it an ideal medical substrate. However, its pure protein material exhibits insufficient coagulation activity and weak antioxidant and antibacterial capabilities, limiting its hemostatic effect when used alone. Plant polyphenols possess excellent procoagulant, antioxidant, antibacterial, and anti-inflammatory properties, and combining plant polyphenols with silk fibroin has become a research hotspot in hemostatic materials in recent years. However, existing composite technologies mostly employ simple solution blending and static molding processes, resulting in disordered molecular assembly, poor stability of polyphenol-protein binding, and problems such as active ingredient detachment and uneven material pore structure. Furthermore, traditional preparation processes often rely on chemical cross-linking agents and high-temperature treatment, which can easily cause protein denaturation and polyphenol inactivation, posing biosafety risks. In addition, existing polyphenol / silk fibroin composite hemostatic materials have a single function, focusing only on hemostatic performance, and cannot simultaneously regulate the wound inflammatory microenvironment, promote angiogenesis and tissue regeneration, and have uncontrollable cross-linking density and degradation cycles that are difficult to adapt to different wound repair rhythms, easily leading to secondary bleeding or inflammatory reactions from foreign bodies in the body, greatly limiting their clinical application.

[0004] Therefore, developing a novel silk fibroin / polyphenol absorbable hemostatic material with controllable structure, excellent performance, and functions of rapid hemostasis, antibacterial and anti-inflammatory effects, controllable degradation, and repair promotion is of great clinical value and industrial significance. Summary of the Invention

[0005] The purpose of this invention is to provide an absorbable hemostatic material based on the self-assembly of plant polyphenols and silk fibroin and its preparation method, aiming to develop a novel absorbable hemostatic sponge material with layered porous structure, controllable structure, and synergistic function. This invention abandons the traditional single-pH static mixing mode and adopts segmented gradient acid-base regulation to induce silk fibroin molecules to gradually transform from random coils to an ordered β-sheet conformation. At the same time, it drives the composite polyphenol molecules to anchor layer by layer in the protein network, forming a two-layer hierarchical porous structure with large pores on the surface for rapid liquid absorption and micropores on the inner layer for blood locking and coagulation. The porosity is controllable, solving the problems of disordered pores, slow liquid absorption, and poor blood locking in traditional materials. It breaks through the single tannic acid polyphenol system and adopts a combination of tannic acid and gallic acid to take into account both rapid coagulation and wound microenvironment regulation. This invention introduces trace amounts of biocompatible iron and calcium composite ions to achieve in-situ dynamic chelation and cross-linking with composite polyphenols, constructing a "protein hydrogen bond network + metal polyphenol chelate network" dual cross-linking system, which significantly improves the wet mechanical strength and wound adhesion of the material. At the same time, calcium ions can actively activate the coagulation pathway, doubly accelerating hemostasis, while iron ions assist in antibacterial and antioxidant effects, resulting in synergistic effects.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: an absorbable hemostatic material based on the self-assembly of plant polyphenols and silk fibroin and its preparation method, characterized in that: the absorbable hemostatic material comprises the following components in parts by weight: 80-120 parts of high-purity silk fibroin solution, 2-10 parts of compound plant polyphenols, 10-30 parts of compound bio-metal ion aqueous solution, and the remainder being deionized water.

[0007] Preferably, the absorbable hemostatic material comprises the following components in parts by weight: 90-100 parts of high-purity silk fibroin solution, 4-6 parts of compound plant polyphenols, 14-20 parts of compound bio-metal ion aqueous solution, and the remainder being deionized water.

[0008] Preferably, the high-purity silk fibroin solution is derived from raw silkworm silk and has a mass fraction of 4% to 6%.

[0009] Preferably, the compound plant polyphenols are prepared from tannic acid and gallic acid.

[0010] Preferably, the composite biometal ion aqueous solution is prepared from ferric chloride solution and calcium chloride solution.

[0011] This invention also provides a method for preparing an absorbable hemostatic material based on the self-assembly of plant polyphenols and silk fibroin, the preparation method comprising the following steps:

[0012] (1) Preparation of high-purity silk fibroin solution: Select high-quality silkworm raw silk, degummed twice with sodium carbonate dilute solution and boiling water for 30 min each time, rinsed repeatedly with deionized water until neutral, and dried at low temperature of 60℃ to obtain pure silk fibroin fiber; use low temperature lithium bromide ternary solution to gently dissolve silk fibroin fiber at 60℃ for 4 h, after dissolution, put it into dialysis bag, dialyze with deionized water for 72 h, change the water every 6 h, after dialysis, centrifuge at low speed to remove precipitated impurities, concentrate to obtain high-purity silk fibroin aqueous solution, and store at 4℃ for later use;

[0013] (2) Preparation of composite polyphenol precursor solution: Tannic acid and gallic acid were accurately weighed at a mass ratio of 3:1, dissolved in sterile deionized water, and magnetically stirred at room temperature in the dark for 30 min to prepare a uniform composite polyphenol solution.

[0014] (3) Gradient pH-induced dynamic self-assembly: Take a silk fibroin aqueous solution, stir at low speed at room temperature, slowly adjust the pH of the system to 5.5 with dilute acetic acid and maintain it for 10 min; add the composite polyphenol precursor solution at a uniform rate, control the addition time to 20 min, adjust the pH of the system to 4.5 after the addition is completed, stir at 30℃ for 40 min, gradually adjust the pH of the system to 6.0, and incubate at constant temperature for 2 h.

[0015] (4) In-situ metal chelation and cross-linking enhancement: Add composite metal ion solution slowly to the self-assembled composite sol, stir at low speed at room temperature for 15 min, and let stand at room temperature for 30 min after the addition is completed;

[0016] (5) Gradient freeze-drying molding: The cross-linked composite sol is poured into a custom mold, spread out evenly, and the thickness is controllable; it is first pre-frozen at -20℃ for 2 hours, then deep-frozen at -55℃ for 6 hours, and finally vacuum freeze-dried for 24 hours to completely remove moisture; after freeze-drying, it is demolded to obtain a double-layer graded porous sponge-like hemostatic material.

[0017] (6) Aseptic activation and packaging: Low-temperature ethylene oxide sterilization is used, followed by vacuum packaging to protect from light and storage at room temperature.

[0018] Preferably, the purity of the high-purity silk fibroin solution obtained in step (1) should be greater than or equal to 98%.

[0019] Preferably, in step (2), to avoid polyphenol oxidative deactivation, the homogeneous solution of the composite polyphenols needs to be prepared and used immediately.

[0020] Preferably, the concentration of the composite metal ion solution in step (4) is 0.01 mol / L.

[0021] The beneficial effects of the present invention using the above structure are as follows: (1) The present invention abandons the traditional single pH static mixing mode and adopts segmented gradient acid-base regulation to induce silk fibroin molecules to gradually transform from random coiling to β-sheet ordered conformation. At the same time, it drives the composite polyphenol molecules to anchor layer by layer in the protein network, forming a double-layer hierarchical porous structure with large surface pores for rapid liquid absorption and micro-pores for blood locking and coagulation. The porosity is controllable, solving the problems of disordered pores, slow liquid absorption, and poor blood locking in traditional materials; (2) The present invention breaks through the single tannic acid polyphenol system and adopts a combination of tannic acid and gallic acid to take into account both rapid coagulation and wound microenvironment regulation; (3) The present invention introduces trace amounts of biocompatible iron and calcium composite ions to achieve in-situ dynamic chelation and cross-linking with composite polyphenols, constructing a "protein hydrogen bond network + metal polyphenol chelation network" double cross-linking system, which significantly improves the wet mechanical strength and wound adhesion of the material. At the same time, calcium ions can actively activate the coagulation pathway, doubly accelerating hemostasis, and iron ions assist in antibacterial and antioxidant effects, with synergistic effects. Attached Figure Description

[0022] Figure 1 Whole blood clotting time.

[0023] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the embodiments of the invention to explain the invention and do not constitute a limitation thereof. Detailed Implementation

[0024] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those familiar to those skilled in the art. Furthermore, any methods and materials similar to or equivalent to those described herein may be applied to this invention. The preferred embodiments and materials described herein are for illustrative purposes only and do not limit the scope of this application.

[0026] Unless otherwise specified, the experimental methods used in the following examples are conventional methods; unless otherwise specified, the experimental materials and test strains used in the following examples were purchased from commercial channels.

[0027] Example 1

[0028] An absorbable hemostatic material based on the self-assembly of plant polyphenols and silk fibroin and its preparation method.

[0029] The absorbable hemostatic material comprises the following components in parts by weight: 90 parts of high-purity silk fibroin solution, 6 parts of compound plant polyphenols, 14 parts of compound bio-metal ion aqueous solution, and the remainder being deionized water.

[0030] The high-purity silk fibroin solution is derived from raw silkworm silk and has a mass fraction of 5%.

[0031] The compound plant polyphenols are prepared from tannic acid and gallic acid.

[0032] The composite biometal ion aqueous solution is prepared from ferric chloride solution and calcium chloride solution.

[0033] This invention also provides a method for preparing an absorbable hemostatic material based on the self-assembly of plant polyphenols and silk fibroin, the preparation method comprising the following steps:

[0034] (1) Preparation of high-purity silk fibroin solution: Select high-quality silkworm raw silk, degummed twice with sodium carbonate dilute solution and boiling water for 30 min each time, rinsed repeatedly with deionized water until neutral, and dried at low temperature of 60℃ to obtain pure silk fibroin fiber; use low temperature lithium bromide ternary solution to gently dissolve silk fibroin fiber at 60℃ for 4 h, after dissolution, put it into dialysis bag, dialyze with deionized water for 72 h, change the water every 6 h, after dialysis, centrifuge at low speed to remove precipitated impurities, concentrate to obtain high-purity silk fibroin aqueous solution, and store at 4℃ for later use;

[0035] (2) Preparation of composite polyphenol precursor solution: Tannic acid and gallic acid were accurately weighed at a mass ratio of 3:1, dissolved in sterile deionized water, and magnetically stirred at room temperature in the dark for 30 min to prepare a uniform composite polyphenol solution.

[0036] (3) Gradient pH-induced dynamic self-assembly: Take a silk fibroin aqueous solution, stir at low speed at room temperature, slowly adjust the pH of the system to 5.5 with dilute acetic acid and maintain it for 10 min; add the composite polyphenol precursor solution at a uniform rate, control the addition time to 20 min, adjust the pH of the system to 4.5 after the addition is completed, stir at 30℃ for 40 min, gradually adjust the pH of the system to 6.0, and incubate at constant temperature for 2 h.

[0037] (4) In-situ metal chelation and cross-linking enhancement: Add composite metal ion solution slowly to the self-assembled composite sol, stir at low speed at room temperature for 15 min, and let stand at room temperature for 30 min after the addition is completed;

[0038] (5) Gradient freeze-drying molding: The cross-linked composite sol is poured into a custom mold, spread out evenly, and the thickness is controllable; it is first pre-frozen at -20℃ for 2 hours, then deep-frozen at -55℃ for 6 hours, and finally vacuum freeze-dried for 24 hours to completely remove moisture; after freeze-drying, it is demolded to obtain a double-layer graded porous sponge-like hemostatic material.

[0039] (6) Aseptic activation and packaging: Low-temperature ethylene oxide sterilization is used, followed by vacuum packaging to protect from light and storage at room temperature.

[0040] The purity of the high-purity silk fibroin solution obtained in step (1) should be greater than or equal to 98%.

[0041] In step (2), to avoid the oxidative deactivation of polyphenols, the homogeneous solution of the composite polyphenols must be prepared and used immediately.

[0042] The concentration of the composite metal ion solution in step (4) is 0.01 mol / L.

[0043] Example 2

[0044] An absorbable hemostatic material based on the self-assembly of plant polyphenols and silk fibroin and its preparation method.

[0045] The absorbable hemostatic material comprises the following components in parts by weight: 100 parts of high-purity silk fibroin solution, 4 parts of compound plant polyphenols, 20 parts of compound biometal ion aqueous solution, and the remainder being deionized water.

[0046] The high-purity silk fibroin solution is derived from raw silkworm silk and has a mass fraction of 5%.

[0047] The compound plant polyphenols are prepared from tannic acid and gallic acid.

[0048] The composite biometal ion aqueous solution is prepared from ferric chloride solution and calcium chloride solution.

[0049] The present invention also provides a method for preparing an absorbable hemostatic material based on the self-assembly of plant polyphenols and silk fibroin, wherein the preparation method is performed in accordance with Example 1.

[0050] Example 3

[0051] An absorbable hemostatic material based on the self-assembly of plant polyphenols and silk fibroin and its preparation method.

[0052] The absorbable hemostatic material comprises the following components in parts by weight: 95 parts of high-purity silk fibroin solution, 5 parts of compound plant polyphenols, 17 parts of compound bio-metal ion aqueous solution, and the remainder being deionized water.

[0053] The high-purity silk fibroin solution is derived from raw silkworm silk and has a mass fraction of 5%.

[0054] The compound plant polyphenols are prepared from tannic acid and gallic acid.

[0055] The composite biometal ion aqueous solution is prepared from ferric chloride solution and calcium chloride solution.

[0056] The present invention also provides a method for preparing an absorbable hemostatic material based on the self-assembly of plant polyphenols and silk fibroin, wherein the preparation method is performed in accordance with Example 1.

[0057] Experimental Example 1

[0058] In vitro coagulation properties of an absorbable hemostatic material based on the self-assembly of plant polyphenols and silk fibroin

[0059] The absorbable hemostatic materials prepared in Examples 1-3 were used as test samples and divided into three groups: Example 1, Example 2, and Example 3. The control group used commercially available hemostatic materials. Performance tests were conducted according to the following methods:

[0060] (1) Set the constant temperature water bath to 37°C for preheating, and place all culture dishes and pipette tips at 37°C in advance for insulation;

[0061] (2) Take the sterilized samples from each group and place them in a petri dish at 37°C;

[0062] (3) Take 0.1 mL of sodium citrate anticoagulated rabbit whole blood and add it evenly to the sample surface;

[0063] (4) Immediately add 0.05 mL of 0.2 mol / L CaCl2 solution to the blood, gently shake the petri dish to mix the calcium ions with the blood, and start timing at the same time;

[0064] (5) Incubate at 37℃, and gently tilt the culture dish every 5 seconds to observe the blood flow. When the blood stops flowing and a complete blood clot appears, stop timing and record the coagulation time of the group.

[0065] (6) Set up 6 parallel samples in each group and take the average value.

[0066] Results analysis: such as Figure 1 As shown, the whole blood clotting time in groups 1-3 of Examples was much shorter than that in the control group, with group 3 of Examples having the shortest clotting time.

[0067] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

[0068] The present invention and its embodiments have been described above. This description is not restrictive, and the accompanying drawings are only one embodiment of the present invention; the actual structure is not limited thereto. In conclusion, if those skilled in the art are inspired by this description and design similar structures and embodiments without departing from the spirit of the invention, such designs should fall within the protection scope of the present invention.

Claims

1. An absorbable hemostatic material based on the self-assembly of plant polyphenols and silk fibroin, characterized in that: The absorbable hemostatic material comprises the following components in parts by weight: 80-120 parts of high-purity silk fibroin solution, 2-10 parts of compound plant polyphenols, 10-30 parts of compound biological metal ion aqueous solution, and the remainder being deionized water.

2. The absorbable hemostatic material based on the self-assembly of plant polyphenols and silk fibroin according to claim 1, characterized in that: The absorbable hemostatic material comprises the following components in parts by weight: 90-100 parts of high-purity silk fibroin solution, 4-6 parts of compound plant polyphenols, 14-20 parts of compound bio-metal ion aqueous solution, and the remainder being deionized water.

3. The absorbable hemostatic material based on the self-assembly of plant polyphenols and silk fibroin according to claim 2, characterized in that: The high-purity silk fibroin solution is derived from raw silkworm silk, with a mass fraction of 4% to 6%.

4. The absorbable hemostatic material based on the self-assembly of plant polyphenols and silk fibroin according to claim 3, characterized in that: The compound plant polyphenols are prepared from tannic acid and gallic acid.

5. The absorbable hemostatic material based on the self-assembly of plant polyphenols and silk fibroin according to claim 4, characterized in that: The composite biometal ion aqueous solution is prepared from ferric chloride solution and calcium chloride solution.

6. A method for preparing an absorbable hemostatic material based on the self-assembly of plant polyphenols and silk fibroin according to claim 5, characterized in that: The preparation method includes the following steps: (1) Preparation of high-purity silk fibroin solution: Select high-quality silkworm raw silk, degummed twice with sodium carbonate dilute solution and boiling water for 30 min each time, rinsed repeatedly with deionized water until neutral, and dried at low temperature of 60℃ to obtain pure silk fibroin fiber; use low temperature lithium bromide ternary solution to gently dissolve silk fibroin fiber at 60℃ for 4 h, after dissolution, put it into dialysis bag, dialyze with deionized water for 72 h, change the water every 6 h, after dialysis, centrifuge at low speed to remove precipitated impurities, concentrate to obtain high-purity silk fibroin aqueous solution, and store at 4℃ for later use; (2) Preparation of composite polyphenol precursor solution: Tannic acid and gallic acid were accurately weighed at a mass ratio of 3:1, dissolved in sterile deionized water, and magnetically stirred at room temperature in the dark for 30 min to prepare a uniform composite polyphenol solution. (3) Gradient pH-induced dynamic self-assembly: Take a silk fibroin aqueous solution, stir at low speed at room temperature, slowly adjust the pH of the system to 5.5 with dilute acetic acid and maintain it for 10 min; add the composite polyphenol precursor solution at a uniform rate, control the addition time to 20 min, adjust the pH of the system to 4.5 after the addition is completed, stir at 30℃ for 40 min, gradually adjust the pH of the system to 6.0, and incubate at constant temperature for 2 h. (4) In-situ metal chelation and cross-linking enhancement: Add composite metal ion solution slowly to the self-assembled composite sol, stir at low speed at room temperature for 15 min, and let stand at room temperature for 30 min after the addition is completed; (5) Gradient freeze-drying molding: The cross-linked composite sol is poured into a custom mold, spread out evenly, and the thickness is controllable; it is first pre-frozen at -20℃ for 2 hours, then deep-frozen at -55℃ for 6 hours, and finally vacuum freeze-dried for 24 hours to completely remove moisture; after freeze-drying, it is demolded to obtain a double-layer graded porous sponge-like hemostatic material. (6) Aseptic activation and packaging: Low-temperature ethylene oxide sterilization is used, followed by vacuum packaging to protect from light and storage at room temperature.

7. The method for preparing an absorbable hemostatic material based on the self-assembly of plant polyphenols and silk fibroin according to claim 6, characterized in that: The purity of the high-purity silk fibroin solution obtained in step (1) should be greater than or equal to 98%.

8. The method for preparing an absorbable hemostatic material based on the self-assembly of plant polyphenols and silk fibroin according to claim 7, characterized in that: In step (2), to avoid the oxidative deactivation of polyphenols, the homogeneous solution of the composite polyphenols must be prepared and used immediately.

9. The method for preparing an absorbable hemostatic material based on the self-assembly of plant polyphenols and silk fibroin according to claim 8, characterized in that: The concentration of the composite metal ion solution in step (4) is 0.01 mol / L.